The Caspian Region as a political object - Musayev, M.G. (Ye.A.Buketov Karaganda State University Publ., 2015)
Each independent state puts foreign policy according to its national interests. The national interests of the state are its territorial integrity, sovereignty and the people's interests and national security. In a democratic society, the Heads of State or Government, for decision-making are trying to strike a balance between national interests and the needs of the population. In foreign policy should reflect the interests of the people. In this sense, the Caspian region is an important object of regional policy for all the countries bordering the Caspian Sea.
Каспий аймағы саясаттың нысаны ретінде
Каспийский регион как объект политики
Keywords: national interests; the Caspian Sea; oil; foreign and domestic policy of Azerbaijan; national security